Review of rheological behaviour of sewage sludge and its importance in the management of wastewater treatment plants. Issue 1 (14th October 2021) - Collivignarelli, M. C.; Carnevale Miino, M.; Bellazzi, S.; Caccamo, F. M.; Durante, A.; Abbà, A.
Abstract: The process operation of wastewater treatment plants (WWTPs) is based on the proper set up of several physical, chemical and biological parameters. Often, issues and problems arising in the process are strictly linked to the rheological behaviour of sewage sludge (SeS). Therefore, rheological measurements, which recently have captured a growing interest, represent an important aspect to consider in the design and operation of WWTPs, especially in the sludge-handling processes. The knowledge of rheological behaviour of SeS represents a crucial step to better understand its flow behaviour and therefore optimize the performance of the processes, minimizing the costs. The SeS are non-Newtonian fluids and, to date, Bingham and Ostwald models are the most applied. This work presents an overview of scientific literature about the rheological properties of SeS and discusses the importance of its knowledge for the management of WWTPs. HIGHLIGHTS: Sewage sludge behaves like non-Newtonian fluids. The rheological properties are strongly influenced by the TSS concentration and type of treatment. Knowledge of the rheological properties of sewage sludge is crucial for the management of wastewater treatment plants. An incorrect attribution of the rheological behaviour leads to the choice of non-optimal operating conditions. Graphical Abstract